Surface plasmon-enhanced fluorescence and surface-enhanced Raman scattering dual-readout chip constructed with silver nanowires: Label-free clinical detection of direct-bilirubin - Sahoo, Smruti R.; Huey-Jen Hsu, Sandy; Chou, Dev-Aur; Wang, Gou-Jen; Chang, Cheng-Chung (Biosensors & bioelectronics, 2022)
It has been found that the direct/total bilirubin ratio (D/T-BIL) is related to the survival rate of COVID-19 pneumonia. The presence of an excessive amount of bilirubin in human blood also causes liver and neurological damage, leading to death. Therefore, upon considering the adverse impact of the presence of excessive bilirubin in human blood, it has become highly imperative to detect bilirubin in a fast and label-free manner. Herein, we designed and constructed a random-crossed-woodpile nanostructure from silver nanowires to form a 3-dimensional plasmonic hotspot-rich (3D-PHS) nanostructure and successfully used it to detect direct bilirubin (D-BIL) in human blood in a label-free manner. The 3D-PHS nanochip provides rich spatial hot spots that are simultaneously responsive to SERS and SPEF effects and consequently, successfully used to measure and characterize D-BIL with a detection limit of ∼10 nM, requiring only 10μL of human serum for rapid screening, which is the first time D-BIL has been detected in a clinically relevant range. This demonstrates a simple, label-free, pretreatment-free potential biosensing technology that can be used in health care units, and further, in the efficient detection of point-of-care testing with a portable spectrometer. •A crossed-woodpile packing from silver nanowires to form a 3-dimensional plasmonic hotspot-rich (3D-PHS) environment.•The 3D-PHS is 3D expansion of LSPR, which can be used to apply for SERS and SPEF simultaneously.•We successfully used 3D-PHS to detect direct bilirubin (D-BIL) with SERS and SPEF effects, simultaneously in human blood.•The D-BIL was directed (1) in a label-free manner (2) requiring only serum (3) with detection limits of ~10 nM.•It is the first-time D-BIL has been detected in the clinically relevant range. (other cases are not from patients).